Hi, I have a question regarding the proof of a fibonacci statement. I need some help understanding the basic concepts working through to the solution of this. If anyone is able to offer me some help I would appreciate it. I will use 'E' as the summation sign.
I need to prove: Ei=1 to N-2Fi=FN-2 (note the i=1 is on the bottom of the summation sign and N-2 is on the top of it)
Now as proofs go, you first need to state what is obviously true and what can be assumed true based upon that. Which I can see that N=1 and N=2 are true. Now for the part that I do not fully understand and I would like some help with: E i=1 to k+1Fi=E i=1 to kFi+Fk+1 //need help with this line hence Fk+2-2+Fk+1 = Fk+3-2 //also help with this line N=k+1 as the final proof.